Stability of encapsulated red dragon fruit (Hylocereus polyrhizus) peel: effects on antioxidant and prebiotic potency - Justina, Fayola; Aditiyarini, Dwi; Ariestanti, Catarina Aprilia (Advances in Food Science, Sustainable Agriculture and Agroindustrial Engineering (AFSSAAE), 2024)
The high consumption of red dragon fruit has led to an increase in red dragon fruit peel waste in the environment, which has potential as a source of natural food coloring and as a prebiotic but is susceptible todegraded. The objective of this study was to determine the best ratio of maltodextrin and gelatin as encapsulant materials to give the highest stability and prebiotic potential of the colorant (betacyanin) in red dragon fruit peel. The stability and prebiotic potential tests were conducted on the encapsulates during 15 days of storage at room temperature in a dark room. The treatment variations included different maltodextrin to gelatin (GM) ratios of 1:1 (GM1), 2:1 (GM2), and 3:1 (GM3). The parameters tested were encapsulation yield, moisture content, betacyanin content, percent inhibition of free radicals, and prebiotic potential using probiotic Lactobacillus bulgaricus (L. bulgaricus). The results showed that encapsulation could maintain the stability of betacyanin pigment during storage. GM1 gave the best overall results with 10.09% moisture content, 93.94% encapsulate yield, 70% solubility, 0.95 mg/L betacyanin content, 36.31% inhibition percentage, and 5.83 x 107 CFU/mL L. bulgaricus growth.